PREGNANT WOMEN’S PERCEPTION OF VACCINATION IN THE MUNICIPALITY OF ANÁPOLIS, GOIÁS: A QUALITATIVE STUDY - Siqueira1, Ludmila Braga de; Silva, Maria Fernandes Gomide Dutra e (CIPEEX, 2025)
Objectives: to understand pregnant women’s perceptions of immunization, analyzing their knowledge about vaccines, the therapeutic itinerary, and barriers to accessing vaccination sites, taking socioeconomic variables into account. Methods: qualitative research conducted in the municipality of Anápolis, Goiás. Ten pregnant women were interviewed using a semi-structured script. The interviews were audio-recorded, transcribed in full, and submitted to content analysis. Results: most pregnant women demonstrated insufficient knowledge about vaccines and the importance of prenatal care. Most of the interviewees were against the COVID-19 vaccine, highlighting the great influence of the media and the lack of dissemination of complete information about vaccines by health professionals. Conclusion: there is a need for the transmission of complete information about the benefits of immunizers to the population, especially by health professionals.